Toxic Indole Diterpenes from Endophyte-Infected Perennial Ryegrass Lolium perenne L.: Isolation and Stability - Priyanka Reddy; Myrna A. Deseo; Vilnis Ezernieks; Kathryn Guthridge; German Spangenberg; Simone Rochfort (Toxins, 2019)
The most potent of the indole diterpenes, lolitrem B, is found in perennial ryegrass (Lolium perenne L.) infected with the endophyte Epichloë festucae var. lolii (also termed LpTG-1). Ingestion causes a neurological syndrome in grazing livestock called ryegrass staggers disease. To enable the rapid development of new forage varieties, the toxicity of lolitrem B and its biosynthetic intermediates needs to be established. However, most of these indole diterpenes are not commercially available; thus, isolation of these compounds is paramount. A concentrated endophyte-infected perennial ryegrass seed extract was subjected to silica flash chromatography followed by preparative HPLC and purification by crystallization resulting in lolitrem B and the intermediate compounds lolitrem E, paspaline and terpendole B. The four-step isolation and purification method resulted in a 25% yield of lolitrem B. After isolation, lolitrem B readily degraded to its biosynthetic intermediate, lolitriol. We also found that lolitrem B can readily degrade depending on the solvent and storage conditions. The facile method which takes into consideration the associated instability of lolitrem B, led to the purification of indole diterpenes in quantities sufficient for use as analytical standards for identification in pastures, and/or for toxicity testing in pasture development programs.